SOLUBLE GENE-EXPRESSED STIMULATING GROWTH FACTOR RECEPTOR 2 AS A POSSIBLE SERUM MARKER OF DIASTOLIC DYSFUNCTION IN PATIENTS WITH HYPERTENSIVE DISEASE AND TYPE 2 DIABETES MELLITUS - Bilovol, O.M.; Knyazkova, I.I.; Kіrіenko, O.M.; Kuzminova, N.V.; Kirіenko, D.O.; Bogun, M.V.; Havryliuk, A.O. (World of Medicine and Biology, 2022)
We examined 60 patients with stage II hypertension (HT), grade 2, mean age 54.7±3.8 years. The first group consisted of 30 patients with hypertension of the II stage, the second group included 30 patients with HT with comorbid moderate, subcompensated type 2 diabetes mellitus (DM). The control group consisted of 20 healthy individuals. All subjects underwent clinical and laboratory examination including the level of soluble growth-stimulating receptor expressed by gene 2 (sST2) in serum, echocardiography with an assessment of mitral Doppler blood flow. It was determined that the serum level of sST2 was significantly (p
Keywords: comorbidity of hypertension and type 2 diabetes mellitus; diastolic dysfunction; soluble growth-stimulating receptor expressed by gene 2